Sleeve Gastrectomy Improves Glycemia Independent of Weight Loss by Restoring Hepatic Insulin Sensitivity - Samir Abu‐Gazala; E. Philip Horwitz; Rachel Ben‐Haroush Schyr; Aya Bardugo; Hadar Israeli; Ayat Hija; Jonathan Schug; Soona Shin; Yuval Dor; Klaus H. Kaestner; Danny Ben‐Zvi (2018)
Bariatric surgery dramatically improves glycemic control, yet the underlying molecular mechanisms remain controversial because of confounding weight loss. We performed sleeve gastrectomy (SG) on obese and diabetic leptin receptor–deficient mice (db/db). One week postsurgery, mice weighed 5% less and displayed improved glycemia compared with sham-operated controls, and islets from SG mice displayed reduced expression of diabetes markers. One month postsurgery SG mice weighed more than preoperatively but remained near-euglycemic and displayed reduced hepatic lipid droplets. Pair feeding of SG and sham db/db mice showed that surgery rather than weight loss was responsible for reduced glycemia after SG. Although insulin secretion profiles from islets of sham and SG mice were indistinguishable, clamp studies revealed that SG causes a dramatic improvement in muscle and hepatic insulin sensitivity accompanied by hepatic regulation of hepatocyte nuclear factor-α and peroxisome proliferator–activated receptor-α targets. We conclude that long-term weight loss after SG requires leptin signaling. Nevertheless, SG elicits a remarkable improvement in glycemia through insulin sensitization independent of reduced feeding and weight loss.